Investigating the Effect of Halal Awareness on Purchase Decision for Halal Products in Indonesia: A Metadata Analysis - Sofyan, Syaakir; Sofyan, A. Syathir; Syamsu, Nur; Mansyur, Abdurrahman (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2023)
The purpose of this study was to examine the development of research on the influence of halal awareness on purchasing decisions for halal products in Indonesia. The method used is meta-analysis by reviewing 9 studies published in 2018-2023 with the help of the OpenMEE application. The results of this study indicate that there is a positive influence from halal awareness on purchase decisions with a p-value obtained of 0.002 and an estimated value of 0.404, which indicates that the strength of the relationship is in the weak category. It was also found that the most significant average effect size was in the halal cosmetics subgroups with a fairly high estimated value so that it was concluded that halal consumer awareness was more visible in the halal cosmetic industry type.